Meningkatkan Hemoglobin pada Ibu Hamil Trimester III dengan Rebusan Bunga Rosella: Increase Hemoglobin in Third Trimester of Pregnancy with Rosella Flower extract - Rifi Wulandari (Poltekkes Kemenkes Palu, 2020)
Anemia during pregnancy is one of the most common disorders in pregnant women in Indonesia. Rosella (Hibiscus sabdariffa) is considered able to increase the hemoglobin levels in pregnant mothers. To analyze the effect of Rosella flower on the increase of Hemoglobin level in pregnant women receiving Fe tablet. This study was a quasi-experiment with a pretest-posttest control group design. 32 participants were selected using accidental sampling, which assigned in the experiment and control group. All samples were pregnant women in the third trimester and receiving iron tablets. Independent t-test and paired t-test were used for data analysis. The result indicated that there was an increase in hemoglobin levels in both the experiment and the control group. The mean increase of hemoglobin levels in the control group was 0.59gr and in the experiment group was 1.11. The hemoglobin levels in the experiment group were higher than the levels in the control group. Independent t-test obtained a p-value of 0.241 indicating that there wasn’t a significant mean difference of hemoglobin levels between the control group and the treatment group. The consumption of rosella combined with Fe tablet showed a significant increase of hemoglobin levels compared to pregnant women. Therefore, it is suggested for midwives to use the result of this research as evidence-practice through counseling for pregnant mothers about the utilization of rosella that can increase hemoglobin levels in pregnant.